Influence of the experimental program of trainings in armsport on the power indexes of basic muscle groups of 16-17-years-old armwrestlers - O. I. Kamaev; D. O. Bezkorovainyi (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The features of influence of the experimental program of trainings are considered in armsport. The program is developed taking into account age-dependent changes in the organism of young sportsmen, features of development of force and power endurance, structure of long-term preparation. The program is directed on development of force and static power endurance of basic muscle groups of sportsmen. In researches took part 30 sportsmen aged 16-17 years old. It is set that the stage of the specialized base training is foreseen by the increase of time on perfection of technique of fight at the table to 15 %. The special attention must be spared the special physical youth development. The block of the specialized training to send to development of explosive force, workings of weak corners, change of character of work is recommended. It is set that trainings with the static loadings are obligatory and in the general volume of loadings must make no less than 20 %. It is necessarily necessary to plan the block of the restoration training for physical and psychological renewal of sportsmen after the conducted setup time and appearance on competitions, exposure and comprehension of sufferet errors and search of methods of their removal.